Hollywood ups ante in copy protection fight. - Avioli, D. (IEEE spectrum)
The little analog-to-digital converters found everywhere in computing and consumer electronics might, if the entertainment industry gets its way, become the new front line against illicit copying of movies and music. Not surprisingly, the industry's proposal to hardwire copy protection into all these converters has provoked a storm of indignation among consumer electronics producers and civil liberties groups. Concerned that movies might be redigitized, with no copy protection. The Motion Picture Association of America (MPAA) wants analog-to-digital converters to recognize a copyrighted video or audio signal and prevent it from being copied. However the MPAA's plan will be hard for others to accept. Royal Philips Electronics, joined by Microsoft and other dissenting consumer electronics companies, has already voiced dissatisfaction with the report. More manufacturers and the companies that incorporate the converters in their products are expected to follow suit and fight the MPAA proposal. Privacy advocates also are up in arms